Gone fishing - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Fishing with traps and pots FAO, 2001. 66 pp. ISBN 9251043078 US$ 16 Euro 17.65